2017
DOI: 10.1111/jopr.12715
|View full text |Cite
|
Sign up to set email alerts
|

Marginal and Internal Fit of CAD/CAM Crowns Fabricated Over Reverse Tapered Preparations

Abstract: Under the conditions of this study, the marginal and internal fit of zirconia crowns fabricated over inverse-tapered preparations is within clinically accepted values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
(132 reference statements)
2
8
1
Order By: Relevance
“…Mejia et al . (2017) investigated the effect of TOC on marginal and internal fit of CAD/CAM crowns and found that the marginal gap significantly decreased as TOC increased, which supports our finding where the 20–30° taper range produced smaller MMGs than the <20° taper range . However, no TOC above 22° was assessed in their study, and therefore cannot be compared to our finding where MMG increased in the >30° taper range.…”
Section: Discussionsupporting
confidence: 56%
“…Mejia et al . (2017) investigated the effect of TOC on marginal and internal fit of CAD/CAM crowns and found that the marginal gap significantly decreased as TOC increased, which supports our finding where the 20–30° taper range produced smaller MMGs than the <20° taper range . However, no TOC above 22° was assessed in their study, and therefore cannot be compared to our finding where MMG increased in the >30° taper range.…”
Section: Discussionsupporting
confidence: 56%
“…The marginal gaps recorded in the four CAD/CAM ceramic materials assessed in this study were all within the range of clinical acceptance (< 120 µm) 21,22 and the values reached for fracture in all groups were above the ranges recorded for occlusal forces in the posterior region (> 500 N). In light of the data, we failed to reject the null hypothesis concerning the internal fit of the four groups but rejected the null hypothesis with regard to fracture resistance since significantly greater values were recorded for e.max.…”
Section: Resultssupporting
confidence: 58%
“…Studies on the marginal fit of zirconia copings fabricated by CAD-CAM have reported measured marginal discrepancies of as low as 10 μm and as high as 160 μm, with most being less than 80 μm [1416]. With regard to full zirconia crown, the studies show marginal discrepancies between 11 μm to 58 μm [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…The marginal fit of zirconia copings produced using different CAD-CAM system has also been investigated [15, 16, 21, 22]. The marginal fit of monolithic zirconia crown was studied with regard to different preparation designs and sintering techniques [17, 18]. However, no studies investigate the effect of different CAD-CAM fabrication methods on the marginal fit of monolithic zirconia crowns; the use of monolithic zirconia crowns is increasing, and therefore a comparison of fabrication methods is justified.…”
Section: Introductionmentioning
confidence: 99%